A facile synthesis of copper nanoparticles supported on an ordered mesoporous polymer as an efficient and stable catalyst for solvent-free sonogashira coupling Reactions. Issue 8 (7th April 2017) - Wang, Kaixuan; Yang, Liping; Zhao, Weiliang; Cao, Linqing; Sun, Zhenliang; Zhang, Fang
Abstract : A facile synthesis of copper nanoparticles supported on an ordered mesoporous polymer was developed for solvent-free Sonogashira coupling reactions. Abstract : A novel mesoporous phenol-formaldehyde resin-supported copper nanoparticles catalyst was prepared using a two-step protocol involving the melt infiltration of copper nitrate hydrates and the subsequent template pyrolysis-induced in situ reduction of Cu(ii ) ions. Notably, this synthetic process effectively saved time and reduced waste because it did not use any solvents, capping reagents, or reducing reagents. The obtained Cu NPs@MP catalysts had large surface areas and narrow pore size distributions. In addition, most of the Cu nanoparticles, with sizes around 3 to 5 nm, were highly dispersed in the pore channels of the mesoporous polymer. In solvent-free Sonogashira reactions for the synthesis of ynones from acyl chlorides and terminal alkynes, this catalyst exhibited much higher catalytic reactivity than commercial Cu powder and mesoporous silica SBA-15-supported Cu nanoparticles. The excellent catalytic performance can be attributed to the synergistic advantages of mesoporous structure, monodispersed Cu nanoparticles and surface hydrophobicity, which stabilized and concentrated the reactants and increased the accessibility of the active sites while decreasing the mass transfer resistance. Meanwhile, the catalyst could be easily recycled and reused at least ten times, showing good stability under solvent-free reaction conditions.